DEVELOPING AI-BASED LEARNING RESOURCES FOR PROFESSIONAL TRAINING INSTITUTIONS (Web of Teachers: Inderscience Research, 2025)
This study explores the process of developing AI-based learning resources designed specifically for professional training institutions. It examines how artificial intelligence technologies can enhance the quality, accessibility, and personalization of vocational education. The research outlines key methods for integrating AI into digital learning materials, such as adaptive learning systems, intelligent tutoring tools, automated assessment, and data-driven feedback. Furthermore, the study highlights the benefits and challenges of implementing AI-powered educational resources within professional training environments. The findings emphasize the potential of AI to improve learners’ skills, support instructors, and optimize training outcomes in modern workforce development.